Surface treatment method for improving releasability of adherent substances and member for improving releasability of adherent substances
A surface treatment forming minute irregularities with specific parameters enhances the removability of adhered substances, addressing the inefficiency of removing paste-like substances and improving hygiene in food processing.
Patent Information
- Application Number
- JP2022047892
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-03-24
AI Technical Summary
Existing technologies fail to effectively remove paste-like substances from surfaces, leading to adhesion, drying, and difficulty in cleaning, resulting in inefficiency and food loss, especially in food processing and handling.
A surface treatment method involving the formation of countless minute irregularities on the surface of components, with specific parameters such as a water contact angle greater than 65° and a kurtosis value less than 3, and uneven pitch and depth ranges, to enhance the removability of adhered substances.
The method significantly improves the removability of adhered substances, preventing them from drying and sticking, allowing for easy cleaning without soaking, reducing food loss and improving hygiene in food handling and processing.
Smart Images

Figure 0007607343000001 
Figure 0007607343000002 
Figure 0007607343000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a technique for imparting predetermined characteristics to the surface of a component by randomly forming an innumerable number of minute recesses on the surface of the component, and in particular to a technique for improving the releasability of adherent materials. [Background technology]
[0002] In order to explore the possibility of applying surface modification technology by forming dimple-shaped micro-convexities and concaves to various fields, the applicants have taken various approaches, such as confirming the effects in various fields of forming countless micro-convexities and concaves on the surface of a member that comes into contact with the treatment object (treatment object contact member).
[0003] The following technology is one of them. For example, conventionally, powders such as edible powders, such as wheat flour, cornstarch, potato starch, matcha powder, cocoa powder, powdered sugar, and curry powder, and pharmaceutical powders (powdered medicines) have been separated (or classified) using sieves, or handled using storage containers such as hoppers or transport parts such as chutes and conveyors.
[0004] These powders adhere to the surfaces of components such as sieves, storage containers, and transport parts, and grow, becoming relatively large lumps that can cause problems such as poor discharge (hopper) or clogging (sieve), which is one of the reasons for reduced production efficiency and an increase in defective products.
[0005] For these reasons, the present inventors have repeatedly conducted various research and experiments, and based on the results of these research and experiments, the present applicants have proposed in Patent Document 1 a technology in which adhesion of powdery, granular, or pasty substances can be suppressed by forming a plurality of minute recesses (minute dimples) on the surface of a member that comes into contact with powdery, granular, or pasty substances (hereinafter also referred to as a contact member) through a fine particle projection process (e.g., fine particle peening process), which is a type of shot material projection process in which shot material is projected. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6416151 [Patent Document 2] JP 2022-034170 A Summary of the Invention [Problem to be solved by the invention]
[0007] Furthermore, the present inventors have discovered new findings while repeatedly conducting various research experiments, which are described in Patent Document 2.
[0008] The finding described in Patent Document 2 is that cleaning properties can be improved (enhanced) by randomly forming countless (multiple) micro-unevennesses (micro-depressions) of predetermined specifications (such as unevenness pitch and recess depth) on the surface of a component, and this technology is a new finding that was not previously known.
[0009] More specifically, a test (experiment) was conducted in which wheat flour paste was applied to the surface of a component (test piece) on which a countless number of dimple-shaped micro-depressions were formed on the surface, and the test piece was then tilted slightly and tap water was poured over the test piece from above to wash the paste off.As a result, it was discovered that among the components (samples or test pieces) on which a countless number of micro-depressions of different specifications were formed on the surface, there were specifications that could improve cleanability.
[0010] Incidentally, effects that have been known to be achieved up until now by forming multiple (infinite) dimple-shaped micro-depressions include suppressing adhesion of powder and sticky substances, and forming an infinite number of micro-concave portions on the sliding surface to function as oil reservoirs, thereby reducing sliding resistance and suppressing wear. However, this effect of improving cleanability is a completely different effect that could not be predicted from these.
[0011] Incidentally, according to the micro-roughness forming process disclosed in Patent Document 2, food residues and the like can be washed away simply by pouring water over them. However, if paste-like food residues are left adhering to the surface of tableware or containers in a food production line, for example, they may dry out and become stuck to the surface.
[0012] When it dries and sticks to surfaces in this way, it becomes impossible to wash it off by simply pouring water over it. For example, when making curry roux or simmering curry at home, curry adheres to the inner walls of pots and other containers and when it dries, it sticks to the walls, becoming unwanted food residue (increasing food waste) and requiring time and effort to wash it off.
[0013] Furthermore, when using dishwashers, if the paste-like food residue dries and adheres to the surface, the dishwasher cannot clean the adhered matter completely, and dirt remains on the surface.
[0014] If the material dries and adheres to the surface in this way, even if you try to wash it by pouring water or warm water over it, the adhered material will remain attached and will not be able to be washed off properly. It will be necessary to soak the material for a relatively long time before washing it, which is very inefficient and difficult to work with, and also leads to the problem of food residue.
[0015] In light of these points, the inventors have conducted various research and experiments, and as a result have discovered a surface treatment method and member that can prevent paste-like substances and the like from drying and causing stuck-on substances to adhere (improving the removability of stuck-on substances).
[0016] The present invention has been made in consideration of the above-mentioned situation, and aims to provide a surface treatment method for improving the releasability of adherent materials on a component, which can improve (enhance) the releasability of adherent materials on the surface of the component by randomly forming countless micro-irregularities of predetermined specifications on the surface of the component, and a component with improved releasability of adherent materials. [Means for solving the problem]
[0017] For this reason, the surface treatment method for improving the removability of adhered matter of a member according to the present invention comprises the steps of: A surface treatment method for improving removability of adherent objects of a member, which improves the removability of adherent objects, which are solid objects in a dried state of a powder containing moisture, from a surface of the member, comprising: Based on a projection process in which shot material is projected onto a surface of a component so that the contact angle of water is greater than 65° and the kurtosis value (Pku) is less than 3, The minimum value of the uneven pitch is 100 μm or more and the maximum value is 400 μm or less, and the minimum value of the depth of the recesses related to the uneven pitch is 2 μm or more and the maximum value is 15 μm or less. Micro unevenness 、 By forming an infinite number of these at random, the releasability of any material adhering to the surface of the component is improved.
[0024] In the present invention, the member may be a metallic or resin mesh member, a metallic or resin plate-like member, or a metallic or resin member with a punched opening.
[0025] The member for improving adherent removal property according to the present invention is A member for improving peelability of adhered matter, which improves peelability of a powder containing moisture from adhered matter that is a solid matter in a dried state, The minimum value of the concave-convex pitch is 100 μm or more and the maximum value is 400 μm or less, and the minimum value of the depth of the concave portion related to the concave-convex pitch is 2 μm or more and the maximum value is 15 μm or less. The component has a surface on which countless micro-convexities and concaves are randomly formed based on a projection process in which shot material is projected, and is characterized in that the water contact angle on the surface is greater than 65° and the kurtosis value (Pku) is less than 3.
[0032] In the present invention, the member may be characterized as being a metallic or resin mesh member, a metallic or resin plate-like member, or a metallic or resin member with a punched opening. Effect of the Invention
[0033] According to the present invention, it is possible to provide a surface treatment method for improving the releasability of adherent materials on a component, which can improve (enhance) the releasability of adherent materials on the surface of the component by randomly forming countless micro-irregularities of predetermined specifications on the surface of the component, and a component with improved releasability of adherent materials. [Brief description of the drawings]
[0034] [Figure 1] 1A is a diagram showing an image before a test for a test for peelability of adhered objects according to one embodiment of the present invention (water-soluble wheat flour was placed on each test piece and placed horizontally), and FIG. 1B is a diagram showing the state after the water-soluble wheat flour was applied and then dried for 14 hours (placed horizontally). [Diagram 2] FIG. 1A shows the surface condition of a test piece (MDS) in which dried water-soluble wheat flour naturally peeled off, and FIG. 1B shows the surface condition of a test piece other than MDS after it was vibrated (after vibration) in the state shown in FIG. 1B. [Diagram 3] 2(A) is a diagram showing the state after the surface of the test piece (MDS) in the state of FIG. 2(A) has been showered with hot water, (B) is a diagram showing the state after the surfaces of each test piece other than MDS in the state of FIG. 2(B) have been showered with hot water, and (C) is a diagram showing the surface state of a comparison (Reference substrate (SUS304 #700)) in the same state. [Figure 4] This is an enlarged view of the surface of a test piece (MDS) where wheat flour dissolved in water was applied and then dried for 14 hours, but the wheat flour did not adhere and peeled off naturally. [Diagram 5] FIG. 1 is a diagram showing an example of measurement results of shape data, irregularity pitch, and irregularity depth of countless minute irregularities (minute recesses) formed randomly on the surface of a test piece (MDS). [Figure 6] 1 is a table summarizing the measurement results of the irregularity pitch, irregularity depth, Ra, Rz, and RSm of the minute irregularities on the surface of each test specimen, and the effect of improving the removability of adherent materials. [Figure 7] 1 is a table summarizing the measurement results of the water contact angle and the kurtosis value (Pku) of the surface of each test piece. [Figure 8]This is a graph showing the kurtosis value (Pku) on the horizontal axis and the water contact angle (°) on the vertical axis with respect to the kurtosis value, water contact angle, and effect of improving the removability of adhered substances. [Figure 9] This is a graph plotting the kurtosis value (Pku) on the horizontal axis and RSm (μm) on the vertical axis with respect to the kurtosis value, RSm (μm), and the effect of improving the removability of adhered material. [Figure 10] FIG. 1A is a schematic diagram illustrating the characteristics of micro-irregularities on a surface that do not have the effect of improving the removability of adhered materials, and FIG. 1B is a schematic diagram illustrating the characteristics of micro-irregularities on a surface that have the effect of improving the removability of adhered materials. [Figure 11] FIG. 2A is a diagram for explaining the contact angle of water on a surface, and FIG. 2B is a diagram for explaining the kurtosis value (Pku). [Figure 12] FIG. 2 is a diagram illustrating average roughness (RSm). [Figure 13] FIG. 2 is a diagram showing a 3D image and surface roughness of a comparative control (Reference substrate (SUS304 #700)) subjected to the same adherent peeling test. [Figure 14] This is a cross-sectional SEM image of a single micro-dimple formed experimentally by a single shot of the media used in the fine particle peening process. [Figure 15] This is an SEM image of a cross section of a recess created by laser processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. Note that the present invention is not limited to the embodiment described below.
[0036] As described above, the present applicants have taken various approaches to explore the possibility of applying surface modification technology by forming dimple-shaped (depressions, approximately concave spherical) micro-depressions to various fields, such as by confirming the effects of forming countless micro-depressions on the surface of a component in various fields.In the course of such approaches, the present inventors have obtained new knowledge that was not previously known.
[0037] Specifically, the inventors conducted a test (experiment) in which they applied wheat flour dissolved in water (wheat flour paste) to the surface of a component (test piece) on which a countless number of dimple-shaped micro-depressions were formed, left in that state for a predetermined period of time (e.g., 14 hours) to dry, and confirmed the state of adhesion of the dried wheat flour paste to the surface (state of peeling from the surface). After that, a test (experiment) was conducted to confirm the degree of peeling by vibrating the test piece. Furthermore, a test (experiment) was conducted in which the test piece was showered with warm water of about 30°C. As a result, it was discovered that among components (samples or test pieces) with a countless number of micro-depressions of different specifications formed on their surface, there are specifications that can improve the releasability (reduce adhesion) of dried wheat flour paste. This finding provides an effect that was not previously known regarding a member having a countless number of randomly arranged minute concaves and convexes (minute concaves) on its surface, and is an effect that could not be predicted based on previous knowledge.
[0038] To explain in more detail, water-dissolved wheat flour (wheat flour paste) made by mixing 40g of wheat flour with 80cc (80g) of water was placed on top of each test piece, and each test piece was left horizontally for a specified time (14 hours) to dry.
[0039] Figure 1(A) shows the state when water-soluble wheat flour was placed on each test piece, and Figure 1(B) shows the state after each test piece was left for 14 hours and the water-soluble wheat flour was dried. Figure 1(B) shows that the adhesion state of the dried water-soluble wheat flour differs depending on the details of the micro-irregularity formation treatment (difference in test piece). In particular, as shown in Figures 1(B) and 4, it was confirmed that the dried water-soluble wheat flour did not adhere to the surface of the test piece (MDS) and peeled off naturally. In addition, MD102, MD101, MD5, MD4, MDW, MDS, and MD200 are names (symbols) that represent the processing contents of the micro-roughness formation processing performed on the surface of the test specimen (SUS304), and these symbols in the figure indicate the test specimens that have been subjected to the processing.
[0040] Next, the peeling state of the dried water-dissolved wheat flour was confirmed from the state shown in Figure 1(B). Figure 2(A) shows the state of the test piece (MDS) where the dried water-dissolved wheat flour naturally peeled off, and Figure 2(B) shows the state of the test piece other than MDS (treatment symbol) after it was vibrated (after vibration) in the state shown in Figure 1(B). Note that here, the vibration was applied by an operator by lightly tapping the edge of the test piece (substrate) with the handle of a precision screwdriver.
[0041] From Figures 2(A) and 2(B), it was confirmed that MDS has extremely high peelability against adhered materials, and that MD5, MD4, MDW, MD200, etc. can also improve the peelability against adhered materials.
[0042] Next, a test was conducted in which the surfaces of the test pieces were showered with hot water from the state shown in Figure 2(A) and Figure 2(B). Figures 3(A) to (C) show the state after the hot water shower. From Figure 3(A), it can be seen that the MDS was thoroughly washed away of any adhering substances by a hot water shower. In addition, from Figure 3(B), it was confirmed that the adhered materials were completely washed away by the hot water shower for MD5, MD4, MDW, and MD200. It was confirmed that the peelability of MD101 and MD102 was only about the same as that of the reference substrate. Figure 3(C) shows an example of the state (same as Figures 3(A) and (B)) after drying and adhering water-dissolved wheat flour to the surface of a reference substrate (SUS304 #700) for comparison, vibrating it, and then rinsing it with a hot water shower. It can be seen that the wheat flour is adhering to the surface as a solid substance.
[0043] Here, the test piece of the reference substrate (SUS304 #700) used for comparison is a stainless steel plate material made of SUS304, the surface of which has been polished with a P700 buff (no fine particle projection treatment was performed), and the surface of the plate material (component) has a glossiness close to that of a mirror. An example of a representative surface 3D image is shown in Figure 13.
[0044] The details of the various micro-irregularity forming processes according to the present embodiment are as follows: a projection material made of SiC (silicon carbide), ceramics, metal, glass, etc., with a particle size of several μm to several hundred μm is sprayed from a spray nozzle onto the surface of a stainless steel plate material made of SUS304 together with compressed air of about 1 / several (for example, 0.1 to 0.5) MPa, and a projection process (projection processing) is performed on the processed surface. A test piece with countless randomly formed micro-irregularities on the surface by such fine particle projection processing (processing) was used for the experiment.
[0045] An example of shape data of countless randomly formed minute irregularities (minute concaves) on the surface of an MDS test piece is shown in Figure 5. As shown in Figure 4, the surface of an MDS test piece has countless randomly formed minute irregularities (minute concaves), and has a matte appearance.
[0046] As shown in Fig. 5, the minimum and maximum values of the unevenness pitch (inlet diameter of the unevenness, interval between the unevenness or interval between the unevenness) of the countless randomly formed minute unevennesses (minute unevennesses) on the surface of the MDS test piece were in the range of about 104.9 to 348.8 μm (in other words, the minimum unevenness pitch was 104.9 μm or more and the maximum unevenness pitch was 348.8 μm or less), and the minimum and maximum unevenness depths related to these pitches were in the range of 3.716 to 13.75 μm (in other words, the minimum unevenness depth was 3.716 μm or more and the maximum unevenness depth was 13.75 μm or less). Considering product variation and measurement error, the minimum and maximum unevenness pitches can be in the range of about 100 to 400 μm, and the unevenness depths related to these pitches can be in the range of about 3 to 15 μm (see Fig. 6).
[0047] In addition, when indicating a range for the size of the unevenness pitch (spacing between convex parts, entrance width of the concave part, opening width, opening diameter) and the depth of the concave part, the range between the minimum and maximum values of the unevenness pitch and the depth of the concave part is indicated.
[0048] Moreover, the surface shape data and 3D surface images in this embodiment, including those described below, were acquired using a shape measuring laser microscope VK-X100 manufactured by KEYENCE Corporation.
[0049] FIG. 6 shows the results of measurements performed on the surface of each test piece in the same manner as MDS, as well as the results regarding the effect of improving the removability of adherent materials. In the figure, Ra is the arithmetic mean roughness defined by the JIS, Rz is the ten-point mean roughness defined by the JIS, and RSm is the average length of the profile curve elements defined by the JIS. Details of RSm are shown in Figure 12.
[0050] As shown in Figure 6, the most effective method for improving the removability of adhered materials was MDS, followed by MDW, and then MD5, MD4, and MD200, which showed consistent effects. No improvement in the removability of adhered materials was confirmed for MD102 and MD101.
[0051] The minimum and maximum values of the irregularity pitch (inlet diameter of irregularity, spacing between protrusions, or spacing between recesses) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MD102 test piece were in the range of 5 to 20 μm (in other words, the minimum irregularity pitch was 5 μm or more and the maximum was 20 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch were in the range of 0.1 to 0.3 μm (in other words, the minimum irregularity depth was 0.1 μm or more and the maximum was 0.3 μm or less).
[0052] The minimum and maximum values of the irregularity pitch (inlet diameter of the irregularity, spacing between convexities, or spacing between concaves) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MD101 test piece were in the range of 5 to 30 μm (in other words, the minimum irregularity pitch was 5 μm or more and the maximum was 30 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch were in the range of 0.1 to 0.6 μm (in other words, the minimum irregularity depth was 0.1 μm or more and the maximum was 0.6 μm or less).
[0053] The minimum and maximum values of the irregularity pitch (inlet diameter of irregularity, spacing between protrusions, or spacing between recesses) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MD5 test piece were in the range of 15 to 60 μm (in other words, the minimum irregularity pitch was 15 μm or more and the maximum was 60 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch were in the range of 0.5 to 3.0 μm (in other words, the minimum irregularity depth was 0.5 μm or more and the maximum was 3.0 μm or less).
[0054] The minimum and maximum values of the irregularity pitch (inlet diameter of irregularity, spacing between protrusions, or spacing between recesses) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MD4 test piece were in the range of 25 to 60 μm (in other words, the minimum irregularity pitch was 25 μm or more and the maximum was 60 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch were in the range of 0.5 to 3.0 μm (in other words, the minimum irregularity depth was 0.5 μm or more and the maximum was 3.0 μm or less).
[0055] The minimum and maximum values of the irregularity pitch (inlet diameter of the irregularity, spacing between protrusions, or spacing between recesses) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MDW test piece were in the range of 100 to 300 μm (in other words, the minimum irregularity pitch was 100 μm or more and the maximum was 300 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch were in the range of 2 to 10 μm (in other words, the minimum irregularity depth was 2 μm or more and the maximum was 10 μm or less). The MDS specimens are described above.
[0056] The minimum and maximum values of the irregularity pitch (inlet diameter of irregularity, spacing between protrusions, or spacing between recesses) of the countless randomly formed micro-irregularities (micro-irregularities) on the surface of the MD200 test piece ranged from 5 to 30 μm (in other words, the minimum irregularity pitch was 5 μm or more and the maximum was 30 μm or less), and the minimum and maximum values of the irregularity depth related to the irregularity pitch ranged from 0.2 to 1.5 μm (in other words, the minimum irregularity depth was 0.2 μm or more and the maximum was 1.5 μm or less).
[0057] Here, from FIG. 6, it can be seen that even if the unevenness pitch and the unevenness depth of the countless randomly formed minute unevennesses (minute concaves) on the surface of the test piece are in the same range, there are differences in the effect of improving the removability of the adhered material.
[0058] Until now, the inventors have confirmed the effect of suppressing powder adhesion by changing the unevenness pitch and the depth of the indentations of countless micro-irregularities (micro-depressions) formed randomly on the surface of a test piece. In the case of powder adhesion, as long as the unevenness pitch and the depth of the indentations of the micro-irregularities (micro-depressions) are in the same range, the obtained powder suppression effect is also at the same level.
[0059] However, the knowledge gained from this test (experiment) showed that the improvement effect on the removability of adhered materials cannot be determined solely by the unevenness pitch or depth of the micro-irregularities (micro-concave). For example, as shown in Figure 6, MD102, MD101, MD5, MD200, etc. have overlapping areas in terms of unevenness pitch and depth, but there are good and bad improvements in the removability of adhered materials.
[0060] Therefore, the present inventors also investigated the water contact angle (wettability) and the kurtosis value (a value indicating the sharpness of the unevenness) of a surface on which minute unevenness was formed. Here, the water contact angle of the surface of the component was obtained (measured) using a portable contact angle meter PCA-11 manufactured by Kyowa Interface Science Co., Ltd. The kurtosis value was obtained (measured) using the aforementioned VK-X100 manufactured by KEYENCE Corporation.
[0061] The results are shown in Figure 7. The contact angle on the surface of the "MD102" test piece was 47.1°, and the kurtosis value (Pku) was 3.45. The contact angle on the surface of the "MD101" test piece was 50.7°, and the kurtosis value (Pku) was 3.36. The contact angle on the surface of the "MD5" test piece was 74.8°, and the kurtosis value (Pku) was 2.88. The contact angle on the surface of the "MD4" test piece was 70.0°, and the kurtosis value (Pku) was 2.38. The contact angle on the surface of the "MDW" test piece was 94.7°, and the kurtosis value (Pku) was 2.40. The contact angle on the surface of the "MDS" test piece was 93.9°, and the kurtosis value (Pku) was 2.09. The contact angle on the surface of the "MD200" test piece was 79.3°, and the kurtosis value (Pku) was 2.82.
[0062] The contact angle of water is one of the indices expressing "wettability" and "hydrophilicity" (see FIG. 11(A)). The kurtosis value (Pku) is one of the indices that indicate the sharpness or peakedness of the height distribution (see FIG. 11(B)). Pku=3: The height distribution is normal. Pku>3: Surface has many sharp peaks and valleys Pku<3: The surface has few sharp peaks and valleys This indicates that. A kurtosis value (Pku) of less than 3 indicates a water-repellent surface, while a value of more than 3 indicates a hydrophilic surface. Due to the nature of the comparative control (SUS304 #700) (mirror surface), it is difficult to express the sharpness and kurtosis value (Pku), so the kurtosis value of the test piece surface of the comparative control (SUS304 #700) is set to Pku = 3, which is a normal distribution.
[0063] FIG. 8 shows the effect of improving the removability of adhered material, plotted with the kurtosis value (Pku) on the horizontal axis and the contact angle of water (°) on the vertical axis. In FIG. 8, the area enclosed by the dashed line (the area where the kurtosis value (Pku) is less than 3 and the contact angle is greater than 65°) is the area (surface) where the releasability of the adhered material is improved.
[0064] Here, based on the results, the effect of improving the peelability of adhered materials was considered. The surfaces that do not have an effect of improving the removability of adherent materials (MD102, MD101) have a contact angle of 65° or less and a kurtosis value (Pku) of 3 or more, and are hydrophilic surfaces. For this reason, as shown in the upper part of Fig. 10(A), dirt containing moisture easily gets into the concaves of the minute unevenness of the surface. Even if the moisture evaporates from this state, the dirt and other components that have gotten into the concaves remain deposited in the concaves and become firmly attached, as shown in the lower part of Fig. 10(A), and it is believed that the attached matter becomes difficult to peel off from the surface and remains attached to the surface. In other words, it is believed that as the dirt components shrink or deform due to drying, the dirt components get caught on the minute irregularities, which makes it difficult for the dirt components to be peeled off from the surface.
[0065] On the other hand, surfaces that have the effect of improving the releasability of adherent materials (MDS, MDW, MD200, MD4, MD5, etc.) have a contact angle of more than 65°, a kurtosis value (Pku) of less than 3, and are water-repellent surfaces. For this reason, as shown in the upper part of Fig. 10(B), dirt containing moisture is less likely to penetrate into the concave parts of the minute unevenness of the surface. Also, when the moisture evaporates from this state, as shown in the lower part of Fig. 10(B), the dirt and other components do not penetrate into the concave parts, so it is thought that the dirt and other components are placed on the convex parts of the minute unevenness or are floating above the surface. It is believed that the shrinkage and deformation of the soiling components due to drying promotes the natural peeling of the adhered matter from the surface, improving the peelability of the adhered matter.
[0066] The present inventors also considered the relationship between the improvement in adherent removal properties and the kurtosis value (Pku) and RSm of the surface on which minute irregularities are formed. FIG. 9 shows a graph plotting the improvement in adhesion removal performance with the kurtosis value (Pku) on the horizontal axis and RSm on the vertical axis.
[0067] In FIG. 9, surfaces with a kurtosis value (Pku) smaller than 3 and an RSm in the range of 100 to 300 μm were surfaces in which the removability of adhered material was greatly improved. However, even if the RSm is lower (such as 25 μm for MD5 or 8 μm for MD200), a certain degree of improvement in the peelability of adherent materials has been observed on surfaces with a kurtosis value (Pku) of less than 3.
[0068] Taking the above into consideration, a surface that can improve the removability of adherent materials is one that has countless randomly formed microscopic irregularities and has a water contact angle of greater than 65° and a kurtosis value (Pku) of less than 3.
[0069] In addition, taking into consideration the shape of the minute irregularities, the irregularity pitch is in the range of 100 to 400 μm, the recess depth associated with the irregularity pitch is 2 to 15 μm, the water contact angle of the surface is greater than 65°, and the kurtosis value is less than 3.
[0070] Furthermore, the surface that can improve the removability of adhered materials is most effective when the RSm of the surface having countless randomly formed minute irregularities is in the range of 100 to 300 μm and the kurtosis value (Pku) is less than 3. However, a certain degree of effect can also be expected for surfaces with RSm in the range of 8 to 300 μm and a kurtosis value (Pku) less than 3.
[0071] As described above, according to this embodiment, a surface treatment method for improving the releasability of adherent materials on a component, which can improve (enhance) the releasability of adherent materials on the surface of the component by randomly forming countless micro-irregularities of predetermined specifications on the surface of the component, and a component with improved releasability of adherent materials can be provided.
[0072] Therefore, with a surface that has been subjected to the micro-roughness formation treatment of this embodiment, even in cases where residues of paste-like ingredients, etc. would have dried and adhered to the surface of tableware or containers in a food production line, etc. in the past, the residues can be peeled off without adhering, thereby reducing the risk of the residues of food, etc. becoming unwanted adherents.
[0073] Furthermore, when residues of paste-like ingredients and the like dry and stick to the surface, even if you try to wash it by simply pouring water or warm water over it, the stuck material remains attached and it becomes impossible to wash it off properly. It becomes necessary to soak the item in water for a relatively long time before washing, which is very inefficient and difficult to work with, and the present invention can contribute to solving such problems.
[0074] As an example of an application of the surface treatment for improving the removability of stuck-on materials according to this embodiment, the residue of food ingredients such as boiled beans, which previously adhered to the inside of a trough (a long, narrow recess) for filling the contents into a packaging bag or to a cylindrical element and became stuck to the surface, can now be easily removed (cleaned), which is beneficial in terms of reducing food waste and in terms of hygiene. In addition, food residue that previously adhered to and became difficult to remove due to adhesion to the surface of punched screens (partitions using punched metal, etc.) can now be easily removed (cleaned), which is beneficial in terms of reducing food waste and improving hygiene.
[0075] In this embodiment, a test was conducted on the removability of stuck materials when water-dissolved wheat flour was dried, but similar results can also be obtained when drying mixed seasonings (including powdered or granular seasonings, curry powder containing oil, etc.), liquid or paste-like seasonings (soy sauce, sauce, ketchup, mayonnaise, etc.), and sticky substances such as spring roll wrappers and udon noodles.
[0076] In this way, it was possible to discover that forming countless micro-convexities (micro-depressions) randomly on the surface of a component improves the releasability of materials adhered to the surface. However, this discovery relates to an effect that was not previously known regarding components having countless micro-convexities (micro-depressions) formed on their surface, and, as described above, is unpredictable based on previous knowledge.
[0077] Based on such new findings, the present invention relates to a member having a surface on which an innumerable number of minute projections and recesses (minute recesses) are randomly formed, and the member is used as a member for improving the releasability of adherent materials.
[0078] In other words, according to the present invention, it is possible to provide a surface treatment method for improving the releasability of adherent materials on a component, which can improve (enhance) the releasability of adherent materials on the surface of the component by randomly forming countless micro-irregularities of predetermined specifications on the surface of the component, and a component with improved releasability of adherent materials.
[0079] In the present invention, the solidified material is not particularly limited, and examples of the solidified material that may be envisaged include various pastes such as flour, liquids or paste-like fluids such as soy sauce, oil, sauce, ketchup, mayonnaise, etc., pastes such as hamburger steak or gyoza base or chunks of minced meat (raw meat), noodles such as udon and pasta, sticky substances such as gyoza skins, etc., and the like, residues of any food that have been dried to a specific degree and turned into a solid material. That is, the present invention has an effect of improving the removability of stuck matter such as food residues containing moisture, oil and other raw materials in any ratio that has been dried to a certain extent.
[0080] Furthermore, in the present invention, the components are not limited to components that come into contact with objects that are to be subjected to various processes, including food processing parts and parts or components used in handling food ingredients, but can be applied to any components that require good releasability of adhered materials, such as components used for food, cooking, industrial, medical, surgical, and medical purposes. That is, the present invention has an effect of improving the removability of adherent substances such as drug residues and cosmetic residues that contain water, oil and other raw materials in any ratio.
[0081] Incidentally, in the present embodiment, it has been described that countless dimple-shaped minute recesses are formed randomly by shot projection processing, but for example, it is also possible to form countless minute projections and recesses randomly by subjecting the surface of the member to chemical polishing (chemical etching) or plasma processing (e.g., argon bombardment processing), etc. However, the present invention is not limited to this, and the minute recesses according to the present invention can also be formed by at least one of chemical etching, plasma processing, shot projection processing, etc., or by an appropriate combination of these. For chemical polishing (chemical etching), it is assumed that an aqueous solution of, for example, acidic agents such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, or iron (III) chloride in any ratio is prepared and used.
[0082] In addition, forming micro-irregularities (micro-depressions) on the surface of a component also includes the formation of a composite irregular shape (composite dimples) on the surface of the component, for example by transfer, using a mold having micro-irregularities (micro-depressions) on its surface formed based on (utilizing) chemical etching, plasma treatment, shot projection treatment, etc.
[0083] Furthermore, the effect of improving the peelability of adherent materials by the micro-irregularity forming process according to this embodiment is believed to be equivalent for stainless steel, regardless of the surface finish specifications of the base material before treatment, such as #400, #700, 2B, etc., and particularly for non-magnetic austenitic stainless steel (SUS303, 304, 316, etc.). The present invention is also applicable to metal materials other than stainless steel (for example, in the case of iron, metals or alloys such as steel (SS400, etc.), aluminum, titanium, etc.).
[0084] The member for improving adherent removal properties according to the present invention may be a resin member, and the material is not particularly limited. For example, it may be made of ceramics or glass, and in the case of a metal member, it may be made of a metal (alloy) such as iron, aluminum, or titanium.
[0085] Furthermore, the member for improving adherent material release properties according to the present invention may be in any shape, such as a block, plate, or sheet, and is not particularly limited in shape or size. For example, it may be a mesh member (net-like member) or plate-like member made of metal or resin, or a punched metal member (member with punched openings) with multiple openings (including resin).
[0086] In addition, the micro-roughness formation process (shot material projection process, micro-dimple process) of this embodiment uses a known injection device to inject media (shot material, abrasive particles) having different specifications (material, size, shape, etc.) as described above while adjusting the conditions, and collide them against the surface of the component that is the target of surface treatment processing, thereby obtaining the desired treated product (MD102, MD102, MD5, MD4, MDW, MDS, MD200, etc.) with different surface shapes (surface textures).
[0087] For example, a blasting device can be used as the injection device, and an example of the blasting device is "PNEUMA BLASTER" (model: SC series, SG series, etc.) manufactured by Fuji Manufacturing Co., Ltd. In addition, for example, the one described in JP 2019-25584 A can be used.
[0088] More specifically, as an injection device for injecting the injected particles toward the surface of the component, a known blast processing device (blast processing device) that injects abrasives (fine particles) together with compressed gas (air, argon, nitrogen, etc.) can be used.
[0089] Commercially available blast processing equipment (blast processing devices) include suction type blast processing equipment that uses the negative pressure generated by the injection of compressed gas to inject abrasives, gravity type blast processing equipment that injects abrasives that drop from an abrasive tank on the compressed gas, direct pressure type blast processing equipment that introduces compressed gas into a tank containing abrasives and combines the abrasive flow from the abrasive tank with the compressed gas flow from a separately provided compressed gas supply source and injects the abrasive flow, and blower type blast processing equipment that injects the direct pressure compressed gas flow on the gas flow generated by a blower unit, and all of these can be used to inject the aforementioned injection particles. Alternatively, a water jet can be used, which sprays a shot at high pressure with a liquid such as water.
[0090] Here, in the present invention, in order to identify the shape or structure of an uneven surface formed by (or based on) a shot material projection process such as a micro-roughness forming process, a micro-dimple process, or a fine particle projection process, a method of identification is used in which countless dimple-shaped micro-roughnesses (micro-depressions and ridge-like convestibules around the depressions, each with its own shape, pitch, and depth) are formed randomly, which is completely different from the geometric and regular uneven shapes formed according to a pre-designed drawing by laser processing or the like. In other words, instead of using the expression "micro-depressions are formed on the surface by (or based on) the shot projection process," a specifying method (expression) such as "countless micro-convexities (or micro-depressions) are randomly formed on the surface of the component" is used. However, in comparison with prior art, it is anticipated that there may be cases in which it will be difficult to adopt the uneven surface formed by the shot projection process as a distinctive identifying method (expression) that distinguishes it from others with the above-mentioned identifying method (expression).
[0091] For this reason, it is conceivable that there will be a situation in which it will be necessary to specify the uneven surface formed by (or based on) the shot material projection process using the specification method (expression) of "forming micro-irregularities on the surface by (or based on) the shot material projection process." Therefore, at the time of filing this application, there existed circumstances in which it was impossible or unrealistic to specify the shape, structure, characteristics, etc. of the micro-irregularities formed by the shot projection process, and there were cases in which it was unavoidable to use the expression "by forming micro-irregularities on the surface by (or based on) the shot projection process (taking into account cases such as transfer)", as will be explained below.
[0092] In the shot projection process, projected particles (media) are collided with the surface to be processed using compressed air at speeds of several tens to over a hundred meters per second, forming irregular, micron-sized, roughly spherical depressions with convex edges over almost the entire surface of the surface to be processed without significant dimensional change. When the media collides to form micro-depressions in the shot projection process, the periphery of the depressions rises in a crater-like manner to form convex portions (see Figure 14). When other media collides with these raised convex portions, they become depressed, resulting in irregular convex portions with irregular heights.
[0093] In contrast, mechanical processes such as laser processing and cutting create regular concave portions and do not create convex portions because they are removal processes (the convex portions are not raised with the formation of the concave portions).For this reason, the height of the convex portions around the minute concave portions in mechanical processes such as laser processing and cutting matches the height of the surface (original material surface) of the processed material (the component being laser processed) (see Figure 15).
[0094] In addition, since the minute projections and recesses formed by the shot projection process are formed in an countless irregular (random) manner, the surface texture (shape) formed by the shot projection process differs from the surface shape (texture) formed by processes such as polishing and grinding, which scrape the surface and create scratches (grooves such as streaks).However, when measured with a surface roughness meter, the two end up with similar numerical values, so it is not possible to distinguish between the two based on surface roughness, etc.
[0095] However, the effects obtained by the surface texture (shape) formed by the shot projection process (such as the effect of suppressing powder adhesion and the effect of improving the removability of stuck-on material) are exceptional and cannot be predicted from the surface texture formed by processes such as polishing and grinding, which scrape and scratch the surface. Furthermore, shot peening, which involves colliding media of the order of several millimeters to impart residual stress and improve the fatigue limit, makes it impossible to predict that a surface subjected to shot projection treatment would have the effect of removing adherent material.
[0096] In this way, the tiny concaves and convexes formed by the shot material projection process are formed in an countless irregular (random) manner, the shapes of the tiny concaves and the convexities surrounding them are irregular, and in light of this irregularity being the source of the effects achieved by the present invention, it is not possible to specify the surface formed by the shot material projection process other than by using the expression "formed by (or based on) the shot material projection process" as a term for specifying the surface texture (shape) formed by the shot material projection process. As described above, at the time of filing this application, there are circumstances that make it impossible or unrealistic to specify the shape, structure, characteristics, etc. of the minute irregularities formed by the shot projection process.
[0097] The present invention is not limited to the above-described embodiment of the invention, and various modifications can be made without departing from the spirit and scope of the present invention. [Industrial Applicability]
[0098] The present invention can improve the removability of adhered substances from the surface of a component by forming countless dimple-shaped micro-depressions on the surface of the component, and is therefore useful and usable in industries where food (ingredient) waste, hygiene, etc. are issues.
Claims
1. A surface treatment method for improving removability of adherent objects of a member, which improves the removability of adherent objects, which are solid objects in a dried state of a powder containing moisture, from a surface of the member, comprising: A surface treatment method for improving the releasability of adherent materials on a member, characterized in that a countless number of minute irregularities are randomly formed based on a projection process in which shot material is projected onto the surface of the member so that the water contact angle is greater than 65° and the kurtosis value (Pku) is less than 3, and the minimum and maximum irregularities are 100 μm or more and 400 μm or less, respectively, and the depth of the recesses associated with the irregularity pitch is greater than 2 μm and 15 μm or less.
2. 2. The method for surface treatment of a member for improving removability of adherent material according to claim 1, wherein the member is a metal or resin mesh member, a metal or resin plate-like member, or a metal or resin member with a punched opening.
3. A member for improving peelability of adhered matter, which improves peelability of a powder containing moisture from adhered matter that is a solid matter in a dried state, A member for improving removability of adherent material, characterized in that the surface of the member has a water contact angle of greater than 65° and a Kurtosis value (Pku) of less than 3, the surface being formed randomly with countless minute irregularities formed by a projection process in which shot material is projected, the minimum irregularity pitch being 100 μm or more and a maximum irregularity being 400 μm or less, and the minimum depth of the recesses associated with the irregularity pitch being 2 μm or more and a maximum depth being 15 μm or less.
4. 4. The member for improving adherent material release property according to claim 3, which is a metal or resin mesh member, a metal or resin plate-like member, or a metal or resin member with a punched opening.
Citation Information
Patent Citations
Multiparty line telephone system
JP1989016151A
Surface-treated metal foil, laminated body, printed wiring board, semiconductor package, electronic apparatus, and method for manufacturing printed wiring board
JP2017061080A
Washability improving surface treatment method and washability improving member
JP2022034170A
Powder contacting member, powder contacting member surface shape forming method and powder contacting member surface shape evaluation method
WO2020183708A1